Legal Position of Cable Subscription Broadcasting Institutions in the Redistribution of Free-to-Air Content - Muhammad, Amin; Hardina, Hardina; Farid, Achmad Miftah (Dinasti Research, 2025)
Broadcasting institutions are broadcasting organizers, including public broadcasting institutions, private broadcasting institutions, community broadcasting institutions or subscription broadcasting institutions, which in carrying out their duties, functions and responsibilities are guided by applicable laws and regulations. The title of this research is “Legal Position of Cable Subscription Broadcasting Institutions in the Redistribution of Free-to-Air Content”. The object of this research is the broadcasting industry organization. The objective of this research is to analyze the legal position of cable subscription broadcasting institutions in the redistribution according to the law. This paper employed the juridical normative method with the statute and literary approaches. The researchers collected data in this research using the semi-structured literature review and documentation techniques. Results showed that Regulation of Subscription Broadcasting Institutions refers to Law Number 32 of 2002 concerning Broadcasting, Government Regulation No. 52 of 2005 on the Implementation of Subscription Broadcasting Institutions and other related laws. It regulates licensing, procedures for establishment, Subscription Broadcasting Institutions obligations, broadcast content, cross-ownership to reporting and administrative sanctions. One of the Subscription Broadcasting Institutions obligations regulated in this Government Regulation is to provide at least 10% (ten per hundred) of the channel capacity to distribute programs from public broadcasting institutions and private broadcasting institutions